Sound’s Puzzle: a game called musical creation (Orfeu, 2017)
By exploring sounds produced by the piano,  young beginners learning the instrument have material to express themselves musically. As in a puzzle where we put the pieces together to form an image, invented and organized by topics, children can form  musical compositions in a game in which they are the protagonists. Their ideas, intentions, and choices are accepted, encouraged and oriented and lead to the acquisition of pianistic and musical language. Using a case study as methodological device, this article aims to reflect on the participation of children in creative processes, based on the fields of Music Education and Childhood Studies. In an educational context marked by artistic language integration , through  an educational approach where  construction of knowledge happens by sharing of  expertise  between teacher-artists and children,  students’ inventions come to life and contribute toward the understanding of  their music-making processes.
Keywords: Music education; Childhood studies; Creative process; Children’s participation; Piano initiation